Ego Status in Transactional Analysis in Bonjol 1 State Middle School - hidayat, rahmat; Prayitno, Prayitno; Netrawati, Netrawati; Sukma, Dina (Universitas Trunojoyo Madura, 2023)
Transactional analysis is behavioral behavior - cognitive supporting activities to optimize individual ego - each individual ego moves our life according to the mind, and we are limited to the five senses, mind and intellect (reason), and also identify ourselves with terms to some degree. So it needs to be overcome in order to help students to understand themselves, the status of ego status that can be reduced in carrying out their roles. The purpose of this study was to obtain general information from information on the Ego Status of Class IX Students of SMP Negeri 1 Bonjol. The method used is a descriptive method in the form of survey research. The sample of this research is 40 students. The results of the analysis showed that grade IX students of SMP Negeri 1 Bonjol achieved the results of 58% child ego in the